Análise morfométrica do forame mandibular em gatos domésticos sem raça definida - Barroso, Rogério Magno do Vale (2005)
The mandibular foramen was evaluated in domestical cats, to its exact localization to support the alveolar mandibular nerve anesthesic block. Thirty adults domestic cat (Felis catus), 5 male and 25 female were study. Six reference points were measured with universal pachimeter, after mandibular colects preparing. LONG (more lateral edge of the condilar process until the firts incisive lower incisive); TRANS (ventral edge of mandibule until dorsal edge between the second pre-molar teeth and the first teeth inferior); FVENTRAL (more rostrail edge of mandibular foramen until the ventral edge of mandibule); ANG (extremity of the edge more rostral mandibular); COND (extremity more rostral mandibular foramen until the medial edge of the mandibulae condilar of process); COR (more rostral edge of mandibular foramen until mandibule condilar process). The results were submited to descritive estatistics analysis and its use T of Student with p=0,05 where observe the best local anesthesic block of inferior alveolar nerve with a needle would to introduce of 4,1 at 4,4 mm mandibule ventral edge and 12,37 at 12,57 mm of angular process.